The first troglobiotic cryptopid centipede (Chilopoda: Scolopendromorpha: Cryptopidae) from the Caucasus - Tuf, Ivan Hadrián; Barjadze, Shalva; Maghradze, Eter (Zootaxa, 2022)
Cryptops (Cryptops) datviensis sp. nov. from Datvi Cave in Georgia, is the first troglobiotic species of the genus Cryptops Leach, 1814 to be described from the Caucasus. The new species morphologically resembles the common epigean Caucasian species Cryptops caucasius Verhoeff, 1934, but differs in typical troglomorphic features, such as elongation of antennae and legs. A key to species of the genus Cryptops from the Caucasus is presented. A list of the invertebrates inhabiting Datvi Cave is provided.